Semen Analysis: An Update - Santosh, Tummidi (Annals of Pathology and Laboratory Medicine, 2023)
Male factor for infertility is responsible in 50% of cases. In recent times there has been a significant deterioration in semen quality due to various lifestyle factors. In the year 2021 WHO has released the 6th ed. of semen analysis manual. The main highlight of the edition is to provide a step-by-step guide for the evaluation of the semen sample for calculation and interpretation of results.